(untitled) (Damascus University Journal of agriculture sciences, 2021)
The study was conducted during 2017-2018 in the laboratory of insect parasites in the department of insect parasites at the Center for Research and Studies of Biological Control in the Faculty of Agriculture, University of Damascus. The study aimed to study the effect of some fixed temperatures (15, 20, 25, 30 and 35 c) on the growth period of stage development egg-pupa, pupa- adult and egg-adult, and account The Sum of Effective Temperatures (SET) and the lower threshold (LDT). The study showed that the duration of the life stages varies according to the temperature, and that there was a linear correlation between the growth rate of the different phases and the temperature. The most growth period of the different stages was at 15 c (32.6 days for the egg-pupa stage, 26.9 days for the pupa -adult, 59.5 for egg-adult phase). (SET) differed according to the stage of growth. It was 1117.647 degrees / day for the egg-pupa, 82.644 degrees / day for the pupa-adult, 200 degrees / day for the egg-adult. The lower threshold (LDT) varied by stage, it was 12.6 c for the egg-pupa stage, 12.47 c for the stage pupa-adult, and 12.4 c for the stage of egg- adult. The results showed that the appropriate field of development and development of the parasite is 25-30 c, and the appropriate temperature is 25 c.